2015
DOI: 10.1186/s12957-015-0642-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biomarkers screened by next-generation RNA sequencing for non-sentinel lymph node status prediction in breast cancer patients with metastatic sentinel lymph nodes

Abstract: BackgroundNon-sentinel lymph node (NSLN) status prediction with molecular biomarkers may make some sentinel lymph node (SLN) positive breast cancer patients avoid the axillary lymph node dissection, but the available markers remain limited.MethodsSLN positive patients with and without NSLN invasion were selected, and genes differentially expressed or fused in SLN metastasis were screened by next-generation RNA sequencing.ResultsSix candidates (all ER/PR+, HER2−, Ki-67 <20 %) with metastatic SLNs selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Pursuant to the next-generation RNA sequencing study by Feng Liang et al [14] in non-SLN-positive group, CYP2A13, KLK11, and CLEC3A demonstrated higher overexpression. Biomarkers identified in this study can provide a new understanding of the mechanism of breast and lymph node involvement, as well as the selection of patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pursuant to the next-generation RNA sequencing study by Feng Liang et al [14] in non-SLN-positive group, CYP2A13, KLK11, and CLEC3A demonstrated higher overexpression. Biomarkers identified in this study can provide a new understanding of the mechanism of breast and lymph node involvement, as well as the selection of patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been indicated that KLK11 expression is regulated by steroid hormones such as estrogen [23] . CLEC3A and KLK11 are not normally expressed in lymph node tissue [14] . Furthermore, there are limited investigations on the presence of this biomarker in metastatic lymph nodes in breast cancer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there is a history of RNA detection in cancers [28,29] , there are methodological difficulties associated with this type of test, because generally it requires working with fresh biological materials, RNase-free reagents and under conditions which protect RNA integrity and prevent contamination with cellular RNase and between samples.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of the SLN was performed by Liang et al [21] in a small study to predict non-SLN status using next generation sequencing: They identified 103 specifically expressed genes in the non-SLN-negative group and 47 in the non-SLN-positive group. Only 2 protein-encoding genes were identified with high expression levels.…”
Section: Models For Prediction Of Nodal Metastasismentioning
confidence: 99%